Factors affecting the recruitment variability of the Norwegian spring-spawning herring (Clupea harengus L.) - Sætre, R.; Toresen, R.; Anker-Nilssen, T. (ICES Journal of Marine Science, 2002)
The Norwegian spring-spawning herring is characterized by large, long-term stock size variations. The main population dynamics mechanism explaining these fluctuations is variation in recruitment. The recruitment to the stock varies by nearly three orders of magnitude. This study examines recruitment variability of herring emphasizing environmental influences on the determination of year-class strength, and on environmental signals indicating recruitment strength, such as conditions for breeding seabird populations. The Atlantic puffin ( Fratercula arctica ) is an important top predator of 0-group herring and its colonies in northern Norway are strategically situated for that purpose. Results from a long-term population study of puffins are incorporated into the study. The year-class strength for the Norwegian spring-spawning herring is predominantly determined before most of the herring larvae have passed the puffin colonies, i.e. in July. The extremely good year-classes, such as 1983, 1991 and 1992, seem to be characterized by very low mortality north of the colonies, i.e. during July–August. Based on the mean temperature in the Barents Sea in January (prior to spawning), the number of high wind speed events off northern Norway in April and the fledging success of puffin, we can predict year-class strength of herring in July.